Capacity calculation of the electrotechnical scheme of discharge gap replacement of the ozonizer in the COMSOL environment; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Isaev Yu. N. Yusup Niyazbekovich; Kolchanova V. A. Veronika Andreevna; Maltsev А. P.; Aksenov V. P. (Numerical simulation of applied problems, 2017)
Title screen